2011
DOI: 10.1007/s10616-010-9331-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green tea powder (Camellia sinensis L. cv. Benifuuki) particle size on O-methylated EGCG absorption in rats; The Kakegawa Study

Abstract: Tea polyphenols, e.g., (-)-epigallocatechin-3-O-(3-O-methyl gallate (EGCG3"Me), (-)-epigallocatechin-3-O-gallate (EGCG), (-)-epigallocatechin (EGC), (-)-epicatechin-3-O-gallate (ECG), and (-)-epicatechin (EC), are believed to be responsible for the beneficial effects of tea. 'Benifuuki', a tea (Camellia sinensis L.) cultivar grown in Japan, is rich in the anti-allergic molecule epigallocatechin-3-O-(3-O-methyl) gallate (EGCG3"Me). Pulverized Benifuuki green tea powder (BGP) is more widely distributed than leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Maeda-Yamamoto suggested that EGCG3″Me showed higher absorption than EGCG after oral administration of Benifuuki tea extract in rats and humans. 15,18) In previous studies, overestimation of the AUC po of EGCG3″Me and other catechins after administration of tea extract could have occurred, because of metabolism from EGCG to O-methyl EGCGs, in rats. 19) In addition, the elimination of EGCG from plasma was reported to be affected by other tea extract catechins.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Maeda-Yamamoto suggested that EGCG3″Me showed higher absorption than EGCG after oral administration of Benifuuki tea extract in rats and humans. 15,18) In previous studies, overestimation of the AUC po of EGCG3″Me and other catechins after administration of tea extract could have occurred, because of metabolism from EGCG to O-methyl EGCGs, in rats. 19) In addition, the elimination of EGCG from plasma was reported to be affected by other tea extract catechins.…”
Section: Discussionmentioning
confidence: 97%
“…15) Briefly, 50 µL of each plasma sample was mixed with 20 µL of 1% ascorbic acid/0.005% EDTA/0.2 M phosphate buffer (pH 6.5), 5 µL of β-D-glucuronidase (15.6 Units), 5 µL of sulfatase (1.25 Units), and 20 µL of water, and subsequently incubated at 37°C for 45 min.…”
Section: Chemicalmentioning
confidence: 99%
“…Pharmacokinetic analyses confirmed that EGCG3”Me has a significantly higher absorption rate from the intestine and a lower rate of disappearance from the blood than EGCG23. Therefore, although the amount of EGCG3”Me in Benifuuki tea is about one-quarter that of EGCG, the blood concentrations of these two catechins after ingestion of Benifuuki tea are almost identical23. This is considered to be the main reason why Benifuuki has greater anti-allergic activity than Yabukita.…”
mentioning
confidence: 96%
“…In vivo and clinical studies have shown that Benifuuki has strong anti-allergic effects2122. Pharmacokinetic analyses confirmed that EGCG3”Me has a significantly higher absorption rate from the intestine and a lower rate of disappearance from the blood than EGCG23. Therefore, although the amount of EGCG3”Me in Benifuuki tea is about one-quarter that of EGCG, the blood concentrations of these two catechins after ingestion of Benifuuki tea are almost identical23.…”
mentioning
confidence: 97%
“…Importantly, the gallate ester group in catechins may be the structural determinant of 67LR binding (3). Meanwhile 67LR was also shown to serve as a receptor for methylated derivatives of EGCg (73,74), which were found present in a unique tea cultivar and have potent anti-allergy activities(75)(76)(77)(78). On the other hand, other binding proteins have also been identified as significant molecules that…”
mentioning
confidence: 99%